Sources of Tax Compliance Costs for Malaysian Corporate Taxpayers - Sapiei, Noor Sharoja; Abdullah, Mazni (Asian Journal of Accounting Perspectives, 2014)
Tax compliance costs are the costs incurred by taxpayers in complying with the tax reporting requirements. This study identifies the sources of tax compliance costs for corporate taxpayers with regards to internal and external components. Utilizing a survey of big corporations in Malaysia, the sources of tax compliance costs is investigated. The internal-external costs ratio was 37 per cent and 63 per cent, respectively, indicating that there is a heavy reliance on external sources. This study therefore concluded that tax compliance activities were mainly handled by external tax professionals and not by the internal tax department of the companies. The findings arising from this study provide valuable information on sources of corporate tax compliance costs for policymakers in the area of taxation, and also to the taxation profession in general.